2020
DOI: 10.1002/chem.202000577
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical History of Polycyclic Musks

Abstract: Musk odorants are ubiquitous in fine perfumery as well as household products, and are divided into four main families, the nitromusks, the macrocyclic musks, the polycyclic aromatic musks, and the alicyclic musks, following their order of appearance on the perfumery market. This article presents the scientific and industrial adventures during the discovery of the seven commercial polycyclic musks, which invigorated the aroma chemistry corporations during the second half of the 20th century, resulting in relent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The importance of musk odorants in perfumery is directly related to their distinctive scent, which is commonly depicted as soft, warm, sweet, animal, combined with their tenacity and longlastingness [1,2] . Among the different families of musks known to date, polycyclic aromatic musks (PCMs), and particularly Galaxolide ( 1 ) (International Flavors and Fragrances Inc. (IFF)) and Tonalide ( 2 ) (Polak's Frutal Works) (Figure 1), are still predominant in terms of tonnage [3] . Vulcanolide ( 3 ), discovered at Firmenich by Charles Fehr in the late 1980s, [4,5] turned out to exhibit additional earthy and powdery facets, while being more tenacious than Tonalide and at least 10 times stronger.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The importance of musk odorants in perfumery is directly related to their distinctive scent, which is commonly depicted as soft, warm, sweet, animal, combined with their tenacity and longlastingness [1,2] . Among the different families of musks known to date, polycyclic aromatic musks (PCMs), and particularly Galaxolide ( 1 ) (International Flavors and Fragrances Inc. (IFF)) and Tonalide ( 2 ) (Polak's Frutal Works) (Figure 1), are still predominant in terms of tonnage [3] . Vulcanolide ( 3 ), discovered at Firmenich by Charles Fehr in the late 1980s, [4,5] turned out to exhibit additional earthy and powdery facets, while being more tenacious than Tonalide and at least 10 times stronger.…”
Section: Figurementioning
confidence: 99%
“…[1,2] Among the different families of musks known to date, polycyclic aromatic musks (PCMs), and particularly Galaxolide (1) (International Flavors and Fragrances Inc. (IFF)) and Tonalide (2) (Polak's Frutal Works) (Figure 1), are still predominant in terms of tonnage. [3] Vulcanolide (3), discovered at Firmenich by Charles Fehr in the late 1980s, [4,5] turned out to exhibit additional earthy and powdery facets, while being more tenacious than Tonalide and at least 10 times stronger. Further investigation revealed that its odor was almost entirely due to the (À )-enantiomer, [6] and two efficient enantioselective syntheses involving the enantioselective protonation of a ketone enolate as a key step were developed.…”
mentioning
confidence: 99%
“…Thus, the scents of musks, castoreum and ambergris are well recognized in the world of perfumery. However, it seems that it is mainly the musky substances that are of particular importance in the formulation of fragrances with musky notes [46], as evidenced by the large number of studies on musk substances, focusing on chemical analysis [47] and synthesis [48,49]. It must be pointed out that musk odors regroup natural and synthetic musks.…”
Section: General Aspects Of Fragrance Classesmentioning
confidence: 99%
“…Many isochromans exhibit anti-inflammatory [31][32][33], antibacterial [34,35], antifungal [36], antioxidant, and antiplatelet [37,38] activities, while some show cytotoxicity toward human cancer cell lines [39,40] and are used in the treatment of migraine headaches [41]. Moreover, isochroman is the nucleus of the commercial fragrance galaxolide [42][43][44], which is present in many products, including surface cleaners, laundry products, cosmetics, and perfumes. Nitrogen-containing heterocycles are important substructures that are found in and synthetic alkaloids [45,46].…”
Section: Introductionmentioning
confidence: 99%